Evaluation of Dapagliflozin's Impact in Type 2 Diabetes Management as A Supplement to Metformin - Salman Azhar, Ahmed Jamal Chaudhary, Syeda Hira Jafri, Umar Ejaz, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: to analyzing the efficacy and safety of dapagliflozin in type 2 diabetics already taking metformin. Methodology: In this observational study at Madinah Teaching Hospital Faisalabad during July 2021 to October 2022, we enrolled 100 cases of either gender with 40-70 yrs, the impact of dapagliflozin 10 mg once daily in diabetics already taking metformin 1.5-2.5 g/day (DAPA + MET), and who had a follow-up visit at 6 months. The effectiveness was measured by the change in HbA1c at baseline at 12 months, as well as the change in BMI, creatinine and microalbumin levels at 6 months. Results: The effect and safety of Dapagliflozin was evaluated in terms of BMI before treatment 11.52+5.87 which reduced to 27.11+8.63 with significant difference, HbA1c(%) before treatment was 8.78+0.68 which reduced to 7.26+0.85 with a significant difference, sCr(μmol/L) was also reduced from baseline 147.76+6.92 to 142.76+6.41, Microalbumin(μg/mg) was 126.60+4.90 before treatment and 124.48+7.42 after treatment, showing a significant reduction. Conclusion: Patients with type 2 diabetes who received dapaglifozin as an add-on medication is found with a significant reduction in their HbA1c level as well as their FBG during a 6-month treatment period. Keywords: Type 2 diabetes